International Financial Statistics, September 2015. - International Monetary Fund. Statistics Dept. (Washington, D.C. : International Monetary Fund, 2015)
This September issue of International Financial Statistics (IFS) is a standard source of statistics on all aspects of international and domestic finance. Official BPM6 Basis Data Availability table is now included in the Balance of Payments and International Investment Position Statistics section of the Introduction. Balance of Payments Statistics Yearbook contains two sections; World and Regional Tables, and Country Tables. The first section presents 21 world and regional tables for major components of the balance of payments, net International Investment Position (IIP), and total financial assets and total liabilities for the IIP. The second section provides detailed tables on balance-of-payments statistics for 189 economies and IIP data for 143 economies.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet